2021
DOI: 10.3389/fimmu.2021.692997
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution and Diversity of Interleukin-17 Highlight an Expansion in Marine Invertebrates and Its Conserved Role in Mucosal Immunity

Abstract: The interleukin-17 (IL-17) family consists of proinflammatory cytokines conserved during evolution. A comparative genomics approach was applied to examine IL-17 throughout evolution from poriferans to higher vertebrates. Cnidaria was highlighted as the most ancient diverged phylum, and several evolutionary patterns were revealed. Large expansions of the IL-17 repertoire were observed in marine molluscs and echinoderm species. We further studied this expansion in filter-fed Mytilus galloprovincialis, which is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…The inflammatory IL-17 cytokines are encoded by a diverse gene family leading to expanded IL-17 repertoires in various marine invertebrates. This can be seen, for example, in the study of 16 mussel genomes, which revealed 379 unique IL-17 sequences and 96 unique IL-17 receptor variants (35). Phylogenetic analysis revealed that all detected invertebrate IL-17 genes, from both annelids and mollusks, are clustered into one group, suggesting a common ancestral gene of these invertebrate IL-17s (31) (Table 2).…”
Section: Cytokinesmentioning
confidence: 89%
See 2 more Smart Citations
“…The inflammatory IL-17 cytokines are encoded by a diverse gene family leading to expanded IL-17 repertoires in various marine invertebrates. This can be seen, for example, in the study of 16 mussel genomes, which revealed 379 unique IL-17 sequences and 96 unique IL-17 receptor variants (35). Phylogenetic analysis revealed that all detected invertebrate IL-17 genes, from both annelids and mollusks, are clustered into one group, suggesting a common ancestral gene of these invertebrate IL-17s (31) (Table 2).…”
Section: Cytokinesmentioning
confidence: 89%
“…The functional role of these conserved cytokines was indicated by their increased expression in response to bacterial stimuli. Most current information for IL-17 comes from phylogenetic studies, identification of related signaling pathways, and effector mechanisms in models of M. galloprovincialis and C. gigas (33)(34)(35). IL-17 plays a crucial role in mucosal immunity in mussels, just like in vertebrates (35), which was first identified in C. gigas (32) and later on in Pinctada fucata (75).…”
Section: Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-17 is of very ancient origin and one of the most conserved cytokines throughout evolution. It is present in many mollusks and is associated with inflammation, particularly in the gut, because IL-17 can be produced by mucosal epithelial cells (81,82). The Th1 (IFN-g, IL-12, TNF-a), Th2 (IL-4, IL-5, IL-13), and Th17 (IL-17, IL-22) cytokine genes were already present during the emergence of cartilaginous fishes (83), indicating that T cells could generate sets of responses as diverse as in mammals.…”
Section: Transcription Factors Underlying Innate-like T Cell Developmentmentioning
confidence: 99%
“…Mussels can use their efficient innate immune system to deal with different pathogenic agents in a specific way (Costa et al, 2009;Balbi et al, 2013). This attribute is supported by the vast genetic variability that characterizes this species, with several expanded immune gene families as immune recognition C1q factors (Gerdol et al, 2011) or pro-inflammatory cytokines as IL-17 (Saco et al, 2021). The recent discovery of mussel genomic organization as a pangenome revealed presence/absence phenomena in the genetic repertoires of these animals, where a core set of genes was accompanied by great amounts of dispensable and variable genes (Gerdol et al, 2020).…”
Section: Introductionmentioning
confidence: 99%